The COVID-19 Pandemic and Gender+ Inequalities in the Czech Republic, Hungary, and Slovakia: The Heteronormativity of Anti- Pandemic Measures and Their Impact on Vulnerable Groups - Vanda Černohorská; Zuzana Očenášová; Agnes Kende (Gender a Výzkum)
Various research studies suggest that women and other vulnerable groups are the ones who were impacted most and who continue to suffer from the economic and social effects of the pandemic. However, these groups have often been omitted from the measures mitigating the pandemic impact due to their invisibility in the policy-knowledge nexus. This article draws on the findings from the international RESISTIRÉ research project, which focuses on how COVID-19 policies impacted gendered inequalities in Europe. Building on feminist institutionalism and an intersectional approach, we contribute to the debate on how existent gender regimes have shaped anti-pandemic policies in the Czech Republic, Hungary, and Slovakia. While examining policy responses, we identified two main meta-frames that are present across the countries in our analysis and that increased gender+ inequalities: the neoliberal model of active citizens that ties the redistribution of aid to labour market activity and the heteronormative family narrative. This narrative has led to those who do not fit within its framework being ignored in policies and to attacks on those groups in an effort to reinforce the narrative's hegemony. The impact of these frames was further amplified by practices of non-inclusive decision-making (in all three countries), where gender expertise was excluded as politicised and biased.